Upacara tradisi Gumbreg Ageng sebagai daya tarik wisata budaya Muntuk, Dlingo, Bantul, Yogyakarta - R. Jatinurcahyo; Yulianto (Journal of Tourism and Economic, 2023)
The tradition ceremony of Gumbreg Ageng is the deliver of thankful feeling to God the Almighty who has given His Blessings that is Rajakaya animals such as cows, buffaloes, horses, and goats which are used to help to maintain good agriculture and reproduce well. One of the function of Gumbreg Animal tradition ceremony is to strengthen the existing noble cultural values which have been long existed for years. The objective of the research is to describe and explore the noble cultural values that is embodied in tradition ceremony of Gumbreg Ageng. The method of the research used descriptive qualitative analysis. The techniques to obtain the data were through interviews, literature reviews, direct observation and documentation i.e. photos as well as resource data from Marsudi, Tukimin bin Kyai Ahmad Monawi, Sumarno and Bayu Endriyanto. The result of the study found out that the noble cultural values which were embodied in tradition ceremony Gumbreg Ageng are the value of religious aspects, the value of respecting ancestors, the social value of the community, economic values and the value of cultural tourism assets. The tradition ceremony of Gumbreg Ageng is one of the cultural and tourism assets in Indonesia, especially in the Special Region of Yogyakarta which contains noble values that need to be preserved and deserves to be developed.